FACTORS AFFECTING INDIGENOUS PROCESSING OF CASSAVA INTO FLOUR (Alibo) AMONG RURAL WOMEN IN SHENDAM LOCAL GOVERNMENT AREA OF PLATEAU STATE, NIGERIA - Abdullahi, I. M.; Danwanka, H. A. (Journal of Agripreneurship and Sustainable Development, 2018)
This study examined the factors affecting of indigenous processing of cassava into flour (Alibo) among rural women in Shendam local government area of Plateau State, Nigeria. The study area was purposively selected and primary data were collected from randomly selected 120 respondents using structured questionnaire. The data were analyzed using descriptive statistics and production function. The results showed that all the respondents (100%) are small scale operators; about 47.50% have formal education, whereas 37.50% have non-formal education. It was further shown that 72.50% of the respondents have 1-10years of experience in indigenous processing of cassava into flour and about 60.83% of them are within the active age range of 21 – 40 years. Quantity of cassava tubers used and water for fermentation were significant at 95.00% level of significance while operating cost was significant at (p<0.01). Resource use efficiency results indicated that all resources used were inefficiently utilized. Cassava tubers used, labour and water were over utilized while operating expenses was underutilized. The main problems militating against traditional cassava processing in the study area include, among others are: high costs of transport, labour and processing implements; poor pricing of products and very small quantities of cassava used per processing. To achieve increased efficiency of local cassava processing in the study area, the study recommended the adoption of policies that will enable the processors improve on their education, grant them increased access to credit, improved processing technologies and increased quantity of cassava per processing operation.